THE INFLUENCE OF MODELLING THE WAY TOWARD THE STUDENTS’ WRITING ABILITY AT FABLE STORY TEXT IN SMP MUHAMMADIYAH 3 MEDAN - Oktavia Lestari P (Jurnal Didascein Bahasa, 2017)
This study aims to determine the effect of modeling model learning the way to the ability to write text fable stories by students of class VIII SMP Muhammadiyah 3 Medan Year Learning 2016/2017. The population of this study is a class of 50 students, consisting of 2 classes. Based on the determination of the selected sample , class VIII A was as the experimental class and VIII B was as the control class. The method used is the experimental method. Based on the results of research, the ability to write fable story text using modeling modeling the way in experiment class was good because 7 students reach the value of 66-79 (32%), while the ability to write fable story text by using conventional learning model / lecture on control class is less because 11 students reach a value of 40-54 (40%). From the result of hypothesis testing where tcount> ttable was dk = (N1+N2)-2=48 by comparing tcount value with table value obtained was higher than t-table that is 13,78>1,78.Keywords : modeling the way, write, fable story text.